Production and acceptability of doughnut prepared from wheat (Triticum aestivum) and soursop (Annona muricata) flour blends - Deedam; Nua Janet
The study was carried out on the production and acceptability of doughnuts prepared from wheat and soursop flour blends. Soursop was processed into flour with wheat flour in the ratios of, 80:20, 70:30, 50:50 and wheat flour used as the control to produced doughnut. Proximate, mineral and sensory analysis of the doughnut were determined using standard methods. The results of the analysis showed a significant (p<0.05) increase in moisture (27.58-35.37%), fat (13.30-18.37%), ash (1.28-2.08%), crude fibre (17.83-24.87%) and crude protein (6.56-8.35%), with a decrease in carbohydrate content (29.50-17.50%) as substitution of soursop flour increased. Mineral composition showed that Iron, Potassium and magnesium were higher in sample D (50% wheat and 50% soursop flour) and lower in sample A (100% wheat flour). Sensory evaluation using the 9-point hedonic scale showed that sample B (80% wheat and 20% soursop) was liked slightly among all the samples. These results showed that doughnuts prepared with soursop flour have a higher nutritional value than those prepared with only wheat flour.